Cyber Crime And Thier Solution (International Journal of Engineering and Computer Science, 2017)
This paper deals with the cyber crime & its realistic facts which blocked our working capability, efficiency& revealed the privacy of victims. This paper also deals with the futuristic cyber crime & its prevention.We are very thankful to Prof. Sitanshu Ray for his tireless support and his lucid way of explaining us thesalient points really helped us to write this paper.